Measurement of radon (222Rn) and thoron (220Rn) concentration of plants (Vegetables) in different locations in Sulaimania City using CR-39 detector - Salih, Najeba F.; Salh, Hemn M.; Hamad, Ari M. (Univ Santander, 2018)
Introduction: Radon is a radioactive gas released from the normal decay of uranium in rocks and soil depending on local geology. Radioactive decay of uranium through radium produces radon. Materials and Methods: In the present work, seventeen plant (vegetables) samples collected from Sulaimania Governorate. The plants have been analyzed and examined to measure the level of radon (Rn-222) and thoron (Rn-220) using plastic track detector (CR-39) for evaluation of radon and thoron concentration in this region. Results and Discussion: The results indicated that the higher and lower radon concentration have been found in Halabjay-con, and in Sulaimani-center, to be (119.72 Bq.m(-3), 3.236 pCi/L), (54.36 Bq.m(-3), 1.469 pCi/L), respectively, and the higher and lower thoron concentration have been found in Qaladza and in Sulaitnani-center, to be (733.66 Bq.m(-3), 19.828 pCi/L), (227.33 Bq.m(-3)C, 9.117 pCi/L), respectively. Radiation level compared with the standard level known by the EPA (4 pCi/L) and190 Bqm''. The concentration of radon in all sample plants is less than international standard level 4(pCi/L) and190 (Bqml, therefore the human in safety. The average effective dose equivalent (EDE) of radon from plants determined was (7.2) 1.1Sv.y'l for all the samples. This is lower than the normal value of (1.3) rnSv:y ' given by EPA. Conclusions: This study showed that the contamination in the plant (vegetables) is normal and is not considered a great radial dose for plants and consequently for humans.
Keywords: Radon; Thoron; Plants; CR-39 Detector